Functional outcomes following anterior resection for colorectal cancer: a needs assessment and proposal of a nurse‐led remote management algorithm - Nguyen, Thuy‐My; Traeger, Luke; Overall, Bronwyn; Sammour, Tarik; Thomas, Michelle (ANZ journal of surgery, 2024)
Aim With the rise of structured, remote follow‐up of colorectal cancers, there is the potential risk of underdiagnosing and undermanaging low anterior resection syndrome (LARS). This cohort study aims to determine the rate of LARS and its patterns of care, with the aim of generating a risk‐stratified management algorithm that can be employed for nurse‐led follow‐up. Method Patients who underwent elective anterior resection for the management of colorectal cancer between 1 January 2017 and 31 December 2021 were sent quality‐of‐life questionnaires (EORTC‐QLQ‐CR29 and LARS score) and surveyed for LARS symptoms and management utilized. Results Out of 70 patients who completed questionnaires, 71.4% had LARS and 42.9% had major LARS. The international Delphi consensus definition identified more patients (n = 50) with LARS than the LARS score (n = 41). Tumours located <8 cm from the anal verge, ULAR, and temporary stoma were predictive of major LARS on univariate analysis. However, only temporary stoma was predictive for LARS (OR 7.89 (1.15–53.95), P = 0.035) and majors LARS (8.14 (1.79–37.01), P = 0.007) on multivariate analysis. Forty‐four percent of patients with LARS did not have input from any health professional for this condition. Consultation with specialist allied health and/or colorectal surgeons ranged from 4% to 22%. Conclusions Our study highlights that with the current remote follow‐up system focused on cancer outcomes a significant proportion of patients with LARS are overlooked, resulting in the underutilization of relevant health professionals and management options. We propose a nurse‐led management algorithm to address this issue while still minimizing surgical outpatient load. This study demonstrates that while most patients develop LARS following anterior resection, few will seek specialist guidance regarding management without prompting. This highlights the need for a streamlined follow‐up algorithm to screen and manage this silent affliction, particularly in the setting of remote non‐surgeon‐led cancer follow‐up.